(untitled) (Transactions of the Association of European Schools of Planning, 2018)
The competencies required for steering urban development sustainably are scattered amongst various disciplines. This is particularly relevant for planners working at the interface of different sub-disciplines, such as transport and land-use planning, exemplified by transit-oriented development (TOD). In this paper, we use Bertolini’s node-place model (NPM) example for TOD to test whether it enables interdisciplinary work to be undertaken in planning education. We tested our hypothesis in two design studios by challenging urban design students to develop their own design brief based on an NPM. The paper is of a dialogic, discursive nature. Students discuss whether or not the NPM enables them to better understand the relationship between transit and urban development and to develop spatial strategies based upon an integrative approach. Our discussion reveals that the NPM cannot necessarily bridge disciplinary boundaries successfully. However, both lecturers and students see value in the model as a didactic instrument.